"Autoimmune Epilepsy": Encephalitis with Autoantibodies for Epileptologists. Issue 3 (May 2017) - Bien, Christian G.; Holtkamp, Martin
Autoimmune encephalitides may account for epilepsies of so far unknown cause. These "autoimmune epilepsies" may respond well to immunotherapy. More than a dozen autoantibodies have been found with this constellation; therefore, broad autoantibody testing of serum-CSF pairs offers the best diagnostic yield. Several particular features raise the suspicion of an autoimmune cause in otherwise unexplained seizure disorders.